The Formation of Classical Islamic Law: Tracing the Development of Legal Sources, Methodologies, and Madhhabs - Mohammad Ahsanul Khuluqi; Chuzaimatus Saadah; Darmawan (LPPM Ma'had Aly Sunan Drajat Lamongan, 2026)
Classical Islamic law represents the foundation of Islamic legal thought and has significantly influenced the development of Islamic jurisprudence from the formative period to the present. Understanding its historical formation is essential for explaining the evolution of Islamic legal methodology and its contemporary relevance. This study aims to analyze the historical formation of classical Islamic law by examining the development of legal sources, methods of legal reasoning (istinbāṭ), and the emergence of the major Islamic legal madhhabs. This research employs a normative legal research design using a library research approach. Historical and conceptual approaches were applied to examine primary sources, including the Qur’an, Hadith, and classical turāth literature, as well as secondary academic publications on Islamic legal history and uṣūl al-fiqh. The collected data were analyzed qualitatively using a descriptive-analytical method. The findings reveal that classical Islamic law developed progressively from the Prophetic period through the era of the Rightly Guided Caliphs, the Umayyad Dynasty, and reached methodological maturity during the Abbasid period. The expansion of legal sources from the Qur’an and Sunnah to ijmāʿ, qiyās, istiḥsān, and maṣlaḥah mursalah, together with the emergence of the Hanafi, Maliki, Shafiʿi, and Hanbali madhhabs, established a comprehensive legal tradition characterized by methodological diversity and intellectual dynamism. The historical formation of classical Islamic law demonstrates that Islamic jurisprudence evolved through the interaction of revelation, juristic reasoning, and socio-political realities. This methodological legacy continues to provide a significant foundation for addressing contemporary legal challenges within the framework of maqāṣid al-sharīʿah.addressing the challenges of modern society.